TEKS CERITA SI PALALOK SEBAGAI UPAYA PEMAHAMAN NILAI-NILAI KEHIDUPAN MELALUI METODE LITERASI KRITIS - Yanda, Diyan Permata (Universitas Ahmad Dahlan, 2018)
This article contains a discussion on the utilization of one of the archipelago text as a material for critical literacy review. Si Palalok is one of the texts of ancient texts originating from West Sumatra in Malay Arabic versions which have also been in the Latin edition. The manuscript of the story in this article is in the Arabic-Malay version found in the Aditiawarman Museum of Padang City in a still-complete physical condition, but there is a text with a lack of clarity. Much of the information contained in the texts of Si Palaloks story is still found in the reality of the people of life so that the younger generation can learn worthy values to use. The method used for text review is using content analysis techniques. The focus of the analysis of the text of the text can be obtained by using the critic literacy method. Through critical literation meth-ods, the reader is not only expected to read or understand the text but also to criticize the messages and the values of life contained therein.